COMPARATIVE ANALYSIS OF PROFITABILITY, FIRM SIZE, AND MARKET SHARE BEFORE AND DURING THE COVID-19 PANDEMIC IN INDONESIA - Rizaldi, Rifqi; Huda, Achmad Nur; Alfiyan, Ahmad; Kholilah, Kholilah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This study examines the differences in stock returns, firm size, and profitability before and during the Covid-19 pandemic. This research is important because COVID-19 impacts the economic sector. The study compared stock returns, company size, and profitability in 617 companies listed on the IDX under the purposive sampling method. The results showed an increase in stock returns during the Covid-19 pandemic, indicating an increase in people's choices to invest in the capital market. In addition, there was a decrease in profitability, leading to a decrease in the company's total assets. This study contributes to the government's response to the pandemic.